Arab Spring and Egypt-United States of America's relations in post-revolution era - Taghdar, Hossein (2019)
Egypt was selected as a country that has experienced drastic changes in government recently; due to a revolution in 2011 in the chain of the Arab Spring revolutions. The advent of the Freedom and Justice Party (FJP), and later the Muslim Brotherhood after the Egyptian revolution in 2011 has had effects on Egypt- United States relationships. Studying these changes can lead to more research on revolutions caused by the Arab Spring in other countries. It can also explain the hegemonic conduct of the United States in Egypt and determine the elements which were effective in the process of the Egyptian revolution. To this end, the researcher made use of qualitative content analysis and studied scholarly published documents and other relevant official news resources that were published on the relationship between Egypt and the United States after the 2011 revolution. In addition to these secondary resources, 12 key informants (ethnic, academic, and administrative elites) were interviewed. To frame the study, the researcher made use of power transition theory and sought the role of domestic and international variables on the Egypt-United States relationship and the United States' attempts to maintain its hegemony in Egypt. The results with a focus on both Obama's administration and Trumps' Administration revealed that several developments had affected the United States' hegemony in Egypt. Among these factors, 1) End of Unique Alliance with the United States, 2) Egypt's cold relationships with Israel, 3) Egypt's reestablishment of relationships with Iran, 4) Suspension of war on terror, 6) the United States' new policy, 7) Egypt's anti-western agenda, 8) military and security factors, and 9) cultural and social factors can be highlighted. Later, the United States' main strategies in maintaining its hegemony in Egypt were discussed. Among these factors, 1) the United States' aid policy, 2) the United States' tolerance policy, 3) aborting FJP, 4) imposing a western culture, and 4) the United States' support of street protests can be mentioned. In conclusion, it can be stated that the relationship between the United States and Egypt was greatly affected by the Egyptian revolution in 2011. However, the United States has tackled this problem through its political decisions and has maintained its hegemony in Egypt. Areas for further research are discussed at the end of the study.